Assessing Work Habits and Discipline: High School Teachers in South Sumatra Province Post In-Service Teacher Professional Education Program (PPG-DALJAB) - Harapan, Edi; Marisya, Fitria; Marsinah, Marsinah; Malini, Sherly; Purwanto, Muhammad Bambang (Gema Wiralodra, 2024)
From the results of the research, it was found that many factors affect the professional competence of a teacher. Two of the most dominant factors influencing professional competence are "work habits and discipline." This study aims to examine the influence of these two variables on the professional competence of teaching teachers after participating in PPG DALJAB. Data-based correlational method obtained from the distribution of questionnaires and observations. Data was collected from the population of secondary school teachers in South Sumatra which amounted to 29,950, while a random sample was taken from 150 teachers who had completed the PPG DALJAB. The results of the study succeeded in proving that the work habits and discipline of secondary school teachers after participating in PPG DALJAB had a positive and significant effect on teaching professional competence, both partially and simultaneously. However, there was no significant difference in the professional competence of teaching teachers after attending PPG DALJAB with the previous one.